Politics of Memory in Polish Decommunization and Vetting Law - Kowalczyk, Maciej (Sensus Historiae, 2019)
In this article, a phenomenon politics of memory, that appears in polish legislation concerning lowering pensions of former Security Service (1956–1990) officers and statute about renaming streets and other objects of public utility, was analyzed. The main task of this article was to find examples of simplifications of history that are made on the grounds of arbitrary decisions. It was also crucial to answer a question: what is the rule of history in a modern world that is full of politics of memory?